PENYULUHAN PEMANFAATAN APLIKASI BANDICAM & GOOGLE CLASSROOM UNTUK PEMBELAJARAN ONLINE DI SMPIT INSAN RABBANI KOTA BEKASI - Malabay, Malabay (Jurnal Pengabdian Masyarakat AbdiMas, 2020)
Implementation of Community Service aimed at SMPIT Insan Rabbani is located at Jl. Ratuboko IV, Kav. Dutakranji, West Bekasi, Bekasi City, West Java, 17134 aims to share knowledge or transfer knowledge regarding the application of video conferencing applications as a support for educational services to teachers, education staff to understand and be able to develop online-based learning according to their needs. The specific target to be achieved is the understanding and ability to apply video conferencing applications effectively and efficiently as a support for SMPIT Insan Rabbani education services in order to be able to adapt to the demands and needs of educationists. The method used is in the form of counseling with practical delivery through the transfer of knowledge and direct practice in the application so that it is truly acceptable and adds to the essence of knowledge and skills of Teachers, Education Staff on Information Technology, Microsoft Powerpoint Applications, Video Bandicam Applications.Â Keywords: Application, Online, Video Conference, Teaching and Learning Process